2013
DOI: 10.1007/82_2013_348
|View full text |Cite
|
Sign up to set email alerts
|

Legionella Phospholipases Implicated in Virulence

Abstract: Phospholipases are diverse enzymes produced in eukaryotic hosts and their bacterial pathogens. Several pathogen phospholipases have been identified as major virulence factors acting mainly in two different modes: on the one hand, they have the capability to destroy host membranes and on the other hand they are able to manipulate host signaling pathways. Reaction products of bacterial phospholipases may act as secondary messengers within the host and therefore influence inflammatory cascades and cellular proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 204 publications
1
27
0
Order By: Relevance
“…Legionella pneumophila, an important intracellular lung pathogen that primarily thrives in environmental amoebae, possesses a variety of phospholipases (1)(2)(3). So far, phospholipases A (PLA) 2 /lysophospholipases A (LPLA) comprising 15 different proteins are the most prominent ones, although three additional phospholipases C and one phospholipase D have been described (1,2,4,5).…”
mentioning
confidence: 99%
“…Legionella pneumophila, an important intracellular lung pathogen that primarily thrives in environmental amoebae, possesses a variety of phospholipases (1)(2)(3). So far, phospholipases A (PLA) 2 /lysophospholipases A (LPLA) comprising 15 different proteins are the most prominent ones, although three additional phospholipases C and one phospholipase D have been described (1,2,4,5).…”
mentioning
confidence: 99%
“…This bacterium is ubiquitous to the environment, and in humans it is an opportunistic pathogen that causes Legionnaires' disease, a severe pneumonia frequently accompanied by acute respiratory distress syndrome (81). L. pneumophila possesses a large variety of about 20 established and potential PLAs (15 enzymes), PLCs (3 enzymes), and PLDs (1 enzyme) (82,83). L. pneumophila PLase activity destroys phospholipids from lung surfactant, which cov- ers small airways, bronchioles, and the alveolar surface and reduces the surface tension, and thereby its activity may contribute to lung disease (84).…”
Section: Acyl Hydrolases: Phospholipases a And Bmentioning
confidence: 99%
“…L. pneumophila PLase activity destroys phospholipids from lung surfactant, which cov- ers small airways, bronchioles, and the alveolar surface and reduces the surface tension, and thereby its activity may contribute to lung disease (84). The most prominent PLA activity of L. pneumophila is PlaB (Table 4) (83).…”
Section: Acyl Hydrolases: Phospholipases a And Bmentioning
confidence: 99%
See 1 more Smart Citation
“…reviewed in Côtes et al, 2008;Djordjevic, 2010;Flores-Díaz et al, 2016;Kuhle and Flieger, 2013;van der Meer-Janssen et al, 2010), surprisingly the phospholipases of malaria parasites as mediators of biomembrane dynamics are hitherto under-investigated. Notwithstanding the limited number of studies that have addressed phospholipase functions to date, they revealed critical roles for these PLhydrolyzing enzymes during the Plasmodium life-cycle.…”
Section: Introductionmentioning
confidence: 99%